Phosphorylation of Mammalian Olfactory Cyclic Nucleotide-Gated Channels Increases Ligand Sensitivity - Müller, Frank (J Neurosci, 1998)
In vertebrate olfactory sensory neurons, odorant receptors couple the sensory signal to the synthesis of the second messenger cAMP. Cyclic nucleotide-gated (CNG) channels are activated by binding of cAMP and conduct a depolarizing receptor current that leads to electrical excitation of the neuron. The sensitivity of olfactory CNG channels for cAMP can be significantly reduced by binding of calmodulin to a regulatory domain that resides within the N-terminus of the α-subunit of the channel. This regulatory domain also contains a consensus phosphorylation sequence for protein kinase C (PKC). We have investigated the effect of channel phosphorylation by PKC and found that phosphorylation increases ligand sensitivity without counteracting modulation of the channel by calmodulin. We have identified the amino acid residue that is phosphorylated by PKC and have localized three isoforms of PKC in olfactory sensory cilia. The results of this study provide information about the control of ligand sensitivity in olfactory CNG channels by an intrinsic regulatory domain, representing both a calmodulin-binding site and a substrate for PKC.